Projected population- and season-dependent impacts of climate change on a migratory songbird in South America - El Hindi, Talita Santos; Jahn, Alex E.; Tuero, Diego T.; Pizo, Marco Aurélio; Da Silveira, Natalia Stefanini (Frontiers in Bird Science, 2023)
Migratory birds depend on resources located in distantly separated ecosystems, potentially making them vulnerable to rapid environmental changes across their range. Yet, we understand little about how such changes may impact birds in different migratory systems, in large part because of a lack of individual-level research throughout their annual cycle and on different continents. The Fork-tailed Flycatcher (Tyrannus savana) is a widely distributed Neotropical bird, whose nominate subspecies is composed of populations that breed at tropical and south-temperate latitudes of South America and then spend the non-breeding season in northern South America. Using movement data collected with light-level geolocators on individual migratory Fork-tailed Flycatchers from breeding populations at tropical and south-temperate latitudes, we evaluated whether different flycatcher populations vary in their vulnerability to future climate change. Results suggest that populations breeding at south-temperate and tropical latitudes will lose at least 22% of their breeding area, with most losses of south-temperate breeding areas occurring in the northern portions of those areas. Both south-temperate breeders and tropical breeders will also lose non-breeding area, with south-temperate breeders experiencing a loss of over a third of their non-breeding area, whereas tropical breeders will lose up to ~16% of that area. These results are the first to demonstrate population-and seasondependent risks to climate change for a migratory bird breeding in the Neotropics, and suggest that mitigating the impacts of climate change for birds in South America will require conservation planning that accounts for both seasonal and regional processes.